Land Conversion and Changes in Agricultural Communities at Cimanuk Subdistrict, Pandeglang Regency - Kusdiane, Susvia Delta; Soetarto, Endriatmo; Sunito, Satyawan (Sodality: Jurnal Sosiologi Pedesaan, 2018)
Cimanuk Subdistrict is known with rice brand called “beras cimanuk”, which is a quality rice-producing area in Pandeglang Regency, but land use due to regional development has affected the lives of farmers, especially the younger generation of local farmers. This study aims to see how the conversion of agricultural land has a significant impact on social change in society, especially in the survival of generations of farmers. Data collection was conducted from April to June 2016 with interview techniques involving 21 informants consisting of tenants, landowners, surrounding communities, and agricultural extension agents. Data analysis was carried out descriptively. The results of the study concluded that land use change affected the declining role of agriculture in the socio-economic life of the community. the fading of the meaning of agricultural land became a driver in the difficulty of realizing the regeneration of farmers in Cimanuk subdistrict